A European Journal of Health Communication in the Age of Open Science - Thomas Friemel; Sarah Geber; Nico Pfiffner; Julia van Weert; Gert-Jan de Bruijn; Doreen Reifegerste (University of Zurich, IKMZ - Department of Communication and Media Research, 2020)
A decade ago, health communication research in Europe was still considered an emerging field. Today, in response to the assiduous efforts of European researchers and scholars, we are proud to present the European Journal of Health Communication (EJHC). As the first journal that is explicitly dedicated to European health communication research, EJHC can be regarded as a further milestone in the establishment of our discipline in Europe. EJHC is based on the principles of open science by making publications openly available without imposing any charges on readers or authors and providing alternatives to the traditional review and publication process. With this editorial, we want to introduce EJHC as a European journal, emphasise the arguments for the set-up of EJHC as a platinum open access journal, illustrate our efforts to improve academic publishing with various innovations, and present the people behind EJHC.